Perubahan kekuatan mampatan konkrit muda terhadap amplitud relatif gelombang ultrasonik - Kamarudin Mohd Yusof,; Mohammad Fauzi Bahari, (2000)
Grade 20 and 30 of young concrete paste with water-cement ratios 0.5 and 0.6 have been studied using ultrasonic wave. The young concrete paste ages between one day and 28 days have been tested with an ultrasonic combined method. Relative amplitude of pressure wave, amplitude A and velocity Vp of the ultrasonic wave parameters have been measured for the compressive strength of the young concrete. Moisture content of the young concrete paste was also been studied to determine its effect on the concrete paste parameters in relation to the compressive strength. The relative amplitude the pressure wave amplitude A and the pressure wave velocity of the ultrasonic wave showed clearly that the parameters varied with the change of the compressive strength. However the effect of moisture on these parameters are also large and therefore the effect of moisture on the measurement should be taken into account